THE PHYSICOCHEMICAL PROPERTIES OF SEVERAL INDONESIAN RICE VARIETIES - Susiyanti Susiyanti; Rusmana Rusmana; Yeyen Maryani; Sjaifuddin Sjaifuddin; Nanang Krisdianto; Mohamad Ana Syabana (SEAMEO BIOTROP, 2020)
Rice has different varieties, with each variety possessing diverse physical and chemical characteristics. The objective of this study was to analyze the physicochemical properties of several Indonesian local rice varieties. The experiment was conducted from March to April 2017 at the Agriculture Applied Technology Laboratory of the Faculty of Agriculture, Universitas Sultan Ageng Tirtayasa and at the Laboratory of Food Analysis Services in the Department of Food Technology, IPB University. Nine local rice varieties from several areas in Indonesia were used as samples, namely Jalahawara, Ciherang, Pandan Wangi, Rojolele, Sokan, Bendang Pulau, Batang Piaman, Cisantana and Sidrap. Their physicochemical characteristics were analyzed based on some criteria such as: physical quality (weight, length, width, form and percentage of chalkiness), chemical content, water content, ash content, fat content, protein content, carbohydrate content, crude fiber content, starch, amylose and amylopectin content. Data obtained were analyzed by one-way ANOVA using a Randomized Block Design. Jalahawara has the highest percentage of chalkiness. Based on the ratio of length and width, Sidrap and Ciherang were categorized as medium type and the others were oval/round. The heaviest and lightest based on the 1000-grain weight of rice were Ciherang and Bendang Pulau, respectively. The water content was about 2-4% for all samples. The highest and lowest amount of ash and fat content were found in Sidrap and Sokan, respectively. The highest and lowest amount of protein content were found in Batang Piaman and Sokan, respectively. The highest and lowest starch content were observed in Pandan Wangi and Ciherang. The content of amylose and amylopectin was the highest in Batang Piaman. The rice samples were categorized into two groups of low and medium levels of amylose. The low level of amylose was observed in Cisantana, Ciherang, Pandan Wangi and Sidrap, while the medium level of amylose was observed in Jalahawara, Sokan, Bendang Pulau, Batang Piaman and Rojolele.